Integrating Network Pharmacology, Transcriptome and Artificial Intelligence for Investigating Into the Effect and Mechanism of Ning Fei Ping Xue Decoction Against the Acute Respiratory Distress Syndrome - Lu, Xiaoxiao; Ma, Wentao; Fan, Baofeng; Li, Peng; Gao, Jing; Liu, Qiuhong; Hu, Chunling; Li, Yong; Yao, Mengying; Ning, Hanbing; Xing, Lihua (Frontiers in Pharmacology, 2021)
Acute respiratory distress syndrome (ARDS) is a high-mortality disease and lacks effective pharmacotherapy. A traditional Chinese medicine (TCM) formula, Ning Fei Ping Xue (NFPX) decoction was demonstrated to play a critical role in alleviating inflammatory responses of lung. However, its therapeutic effectiveness in ARDS and active compounds, targets, and molecular mechanisms remain to be elucidated. The present study investigated the effects of NFPX decoction on ARDS mice induced by lipopolysaccharides (LPS). The results revealed that NFPX alleviated lung edema evaluated by lung ultrasound, decreased lung Wet/Dry ratio, the total cell numbers of bronchoalveolar lavage fluid (BALF), and IL-1β, IL-6, TNF-α levels in BALF and serum, and ameliorated lung pathology in a dose-dependent manner. Subsequently, UPLC-HRMS was performed to establish the compounds of NFPX. A total of 150 compounds in NFPX were unambiguously characterized. Moreover, integrating network pharmacology approach, transcriptional profiling of lung tissues and artificial intelligence analysis were performed to predict the underlying mechanism. 37 active components and 77 targets were screened out, and herbs-compounds-targets network was constructed. Differentially expressed genes (DEGs) were identified from LPS-treated mice compared with LPS combined with NFPX mice. GO, KEGG and Artificial intelligence analysis indicated that NFPX might act on various drug targets. At last, potential targets, HRAS, SMAD4 and AMPK were validated by qRT-PCR in ARDS murine model. In conclusion, we prove the efficacy of NFPX decoction in treatment of ARDS. And integrating network pharmacology, transcriptome and artificial intelligence analysis contributes to illustrate the molecular mechanism of NFPX decoction on ARDS.